Charge transfer effect on local lattice distortion in a HfNbTiZr high entropy alloy. (October 2021) - Meng, Fanchao; Zhang, Wenyan; Zhou, Zhukun; Sheng, Ruixin; Chuang, Andrew C.-P.; Wu, Chongchong; Huang, Hailiang; Zhang, Shangzhou; Zhang, Hua; Zhu, Lilong; Jiang, Liang; Liaw, Peter K.; et al.
Abstract: It is often assumed that atoms are hard spheres in the estimation of local lattice distortion (LLD) in high-entropy alloys (HEAs). However, our study demonstrates that the hard sphere model misses the key effect, charge transfer among atoms with different electronegativities, in the understanding of the severely distorted local structure in the body-centered cubic (BCC) HfNbTiZr HEA. Through the characterization and simulations of the local structure of the HfNbTiZr HEA, we found that the LLD regions in HfNbTiZr have larger average size compared with face-centered cubic (FCC) HEAs, but the magnitude of LLD significantly varies from one atomic site to another because of electron transfer from larger atoms, Hf and Zr, to smaller ones, Nb and Ti. Our finding may form the basis for the design of high performance HEAs through tuning their site-to-site chemical heterogeneity. Graphical abstract: Image, graphical abstract